Análisis de sensibilidad técnica y económica aplicados a construcción. - Roque-Siles, César (Instituto Tecnológico de Costa Rica, 2007)
Construction is an activity subject to contingencies during the project execution stage. In large construction works, it is also subject to changes in the market during the constructive period. This document presents a method to estimate the most probable condition for a project, taking into account the factors that are more likely to affect it in relation to time and cost. The objective is to analyze the variables that could interfere in the constructive process and to examine the probability of occurrence of one event or another. At the end, a randomized probabilistic combination of the variables will generate the scenario that better conforms to the maximum risk limits established by the company for its projects. This document compiles the experience of the Feasibility Budget department of the Costa Rican Electricity Institute (I.C.E.) and combines it with some concepts found in literature and the Internet. The obtained method was applied to a tunnel construction case that, in spite of being hypothetical, is based on background information of hydroelectric projects. For this purpose, the method was adapted by means of two very-well known software programs, MSProject and @Risk. The use of this method allowed obtaining a project whose duration and cost respond to a probability to succeed, thus reflecting the applicability of the proposed method.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2007.
Keywords: MSProject; Determinístico; Estadístico; Riesgos